Effect of Pregabalin Use as Preemptive Analgesia after Abdominal Hysterectomy on Heart Rate and Arterial Pressure (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Effect of pregabalin on heart rate and arterial pressure is important in its use as preemptive analgesia. Objective: The purpose of the present study was to evaluate the effect of pregabalin use as preemptive analgesia after abdominal hysterectomy on heart rate and arterial pressure.Methodology: This randomized double-blind placebo-controlled clinical trial was conducted in the Department of Anesthesia, Analgesia and Intensive Care Medicine, Banghabandhu Sheikh Mujib Medical University, Dhaka from July 2010 to June 2012 for a period of two years. Women aged between 40-60 years scheduled for abdominal hysterectomy under sub-arachnoid block were selected as study population for this study. A total of one hundred and twenty women meeting the above mentioned criteria were randomly allocated into two equal groups by card sampling. 120 cards, 60 for each group were prepared by another person who was not aware of the study. Group A was known as study group who were received 300mg oral pregnabin one hour before performance of SAB and group B was known as control group who were received matching placebo one hour before SAB. The patients were examined preoperatively and preoperative baseline parameters including heart rate, mean arterial pressure were recorded immediately before sub-arachnoid block (SAB). Patients were visited by the investigators at ½, 1, 2, 4, 12, and 24 h after operation. In each visit, heart rate and mean arterial pressure were measured and were recorded. Result: The present study was conducted on 120 women undergoing abdominal hysterectomy. Of them, 60 received preemptive single oral doses (300mg) Pregabalin (Group A) and the rest 60 received matching placebos (Group B) 1hr before surgery. The mean heart rate with SD before SAB was 79.4±4.7 and 90.5±5.7 in group A and B respectively (p=0.011). After 24 hours of operation the mean heart rate with SD was 73±5 and 85±4 in group A and B respectively (p= 0.043). The mean arterial pressure with SD before SAB was 94.3±5.3 and 95.8±20.4 in group A and B respectively (p=0.569). After 24 hours of operation the mean arterial pressure with SD was 89.4±4.45 and 96.1±2.56 in group A and B respectively (p